Problems of the arbitral legal proceedings in Ukraine - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article examined the issues of arbitration courts in resolving of commercial disputes.